PSPLIB - a project scheduling problem library - Rainer Kolisch; Arno Sprecher (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1996)
We present a set of benchmark instances for the evaluation of Solution procedures for single- and multi-mode resource-constrained project scheduling problems. The instances have been systematically generated by the Standard project generator ProGen. They are characterized by the input-parameters of ProGen. The entire benchmark set including its detailed characterization and the best solutions known so-far are available on a public ftp-site. Hence, researchers can download the benchmark sets they need for the evaluation of their algorithms. Additionally, they can make available new results. Depending on the progress made in the field, the instance library will be continously enlarged and new results will be made accessible. This should be a valuable and driving source for further improvements in the area of project type scheduling.
Keywords: 650; Projektmanagement; Datenbank; Theorie